UJI AKTIVITAS ANTIBAKTERI PADA MACAM MACAM MADU PADA BAKTERI ESCHERICHIA COLI DAN STAPHYLOCOCCUS AUREUS DENGAN METODE DIFUSI AGAR DAN DILUSI CAIR - Siti Aisyah Ratna Putri; Haryanto Susanto; Sabrina Handayani Tambun; Teguh Oktiarso (Fakultas Sains Dan Teknologi Universitas Ma Chung, 2022)
This study is an experimental laboratory, conducted to get the antibacterial activity in the types of multiflora honey, randu honey, mente honey, rambutan honey, sono honey, acacia honey, rubber honey. In this study, preliminary tests, phytochemical screening, and antibacterial tests have been carrying out to determine the Minimum Inhibitory Level (MIC) and Minimum Killing Rate (KBM) at concentrations of 20, 25, 50, and 100%. Phytochemical test results it's known that each honey contains positive alkaloids, flavonoids, glycosides, and saponins. Antibacterial test results showed that each honey's positively had antibacterial activity. MIC and KBM obtained showed that each honey can inhibit the growth of bacteria, but only rambutan honey in Escherichia coli bacteria cannot kill bacteria. Keywords: antibacterial, honey, MIC, KBM, E.coli, S.aureus, disc diffusion, dilution